2012
DOI: 10.1016/j.jacc.2012.08.964
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Platelet Reactivity With Prasugrel 5 mg in Low-Body-Weight Patients Is Noninferior to Prasugrel 10 mg in Higher-Body-Weight Patients

Abstract: In aspirin-treated patients with CAD, prasugrel 5 mg in LBW patients reduced platelet reactivity to a similar extent as prasugrel 10 mg in HBW patients and resulted in greater platelet inhibition, lower HPR, and similar bleeding rates compared with clopidogrel. (Comparison of Prasugrel and Clopidogrel in Low Body Weight Versus Higher Body Weight With Coronary Artery Disease [FEATHER]; NCT01107925).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 8 publications
0
42
0
2
Order By: Relevance
“…Because of the recent demonstration of pharmacodynamic non-inferiority for prasugrel 5 mg in patients <60 kg or aged ≥75 years compared to 10 mg in patients weighing ≥60 kg or <75 years, respectively, a separate analysis considering 5 mg prasugrel as an option in these 2 groups (eg, low weight, elderly) was also performed. 14, 15 Finally, although not an endpoint of this study, 1-month outcomes are also presented. Standardized case report forms (CRFs) were completed.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the recent demonstration of pharmacodynamic non-inferiority for prasugrel 5 mg in patients <60 kg or aged ≥75 years compared to 10 mg in patients weighing ≥60 kg or <75 years, respectively, a separate analysis considering 5 mg prasugrel as an option in these 2 groups (eg, low weight, elderly) was also performed. 14, 15 Finally, although not an endpoint of this study, 1-month outcomes are also presented. Standardized case report forms (CRFs) were completed.…”
Section: Resultsmentioning
confidence: 99%
“…14, 15 Age and body weight may also differ on average from Caucasian populations, knowing that in the FEATHER trial 16 5 mg prasugrel in low body weight patients provided a similar level of platelet inhibition to 10 mg prasugrel in higher body weight patients. The Asian population also displays a higher PD response to prasugrel and ticagrelor with higher exposure to the active metabolite than do Caucasians, 17 suggesting that these drugs are not suitable at the standard dose regimens.…”
mentioning
confidence: 99%
“…A pharmacokinetic sub-study of TRITON-TIMI 38 [37] showed that patients b60 kg or ≥75 years old had higher levels of the active metabolite of prasugrel than other subjects. In these subjects, decreasing the maintenance dose of prasugrel to 5 mg reduced the levels of the active metabolite [38]. In medically-managed ACS patients older than 75 years, post-hoc analysis of the TRILOGY ACS trial showed that 5 mg of prasugrel daily had a similar risk-efficacy profile to 75 mg of clopidogrel daily [39].…”
Section: Benefits and Risks For Specific Subgroupsmentioning
confidence: 99%